Implementation of Religious Moderation Values in the Learning of Islamic Education - Solahudin, Deni; Komala, Ela; Ruswandi, Uus; Arifin, Bambang Syamsul (Al-Hayat: Journal of Islamic Education, 2023)
This research is motivated by the need to teach the values of religious moderation at the senior secondary education level as a response to the phenomenon of spiritual understanding of some groups in Indonesian society, which tend to be extreme. Considering that at the senior secondary education level, entering an age vulnerable to influences both from within and outside education. Therefore, it is essential to internalize the purpose of this research, especially in the Madrasah Aliyah (MA) environment. Otherwise, a qualitative approach with a field study research design will gradually lead to national instability. Data were obtained through observation, interviews and documentation of actual conditions and facts that occurred in the field, supported by books, the latest journals and other sources in the form of related information. Data analysis was performed by condensation, presentation and verification. The implementation of religious moderation is pursued in 4 strategies, namely, First, insert moderation content in each lesson. It is second, optimizing the learning approach. Third, organizing specific programs, education, training and debriefing. Fourth, the teacher makes observations simultaneously. The implementation of religious moderation within Madrasah Aliyah (MA) Al-Huda has been running, realized in textbooks of integral and interconnected subjects, starting from regulation to the level of learning.